2016
DOI: 10.1111/liv.13332
|View full text |Cite
|
Sign up to set email alerts
|

The preventive effect of sustained physical activity on incident nonalcoholic fatty liver disease

Abstract: This study shows an independent protective effect of PA at baseline on incident NAFLD after 4-year follow-up. Furthermore, sustained or increased PA had a preventive effect on incident NAFLD independent of VAT and IR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…In this study, smoking and alcohol consumption along with high BMI were associated with NAFLD, which is consistent with the results of previous studies on the relationship between smoking, [30,31] alcohol [4], [22] and BMI [1], [6], [22], [32] and NAFLD. The onset and progression of NAFLD, apart from the quantity and quality of food and exercise, are also associated with other aspects of lifestyle, including alcohol consumption less than 20 g/day [22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, smoking and alcohol consumption along with high BMI were associated with NAFLD, which is consistent with the results of previous studies on the relationship between smoking, [30,31] alcohol [4], [22] and BMI [1], [6], [22], [32] and NAFLD. The onset and progression of NAFLD, apart from the quantity and quality of food and exercise, are also associated with other aspects of lifestyle, including alcohol consumption less than 20 g/day [22].…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the study by Imaizumi [28] did not report the relationship between skipping breakfast and NAFLD, which is in line with our study. Various studies have been reported a positive relationship between consuming carbohydrate as well as sweets and NAFLD [1], [30], [35].…”
Section: Discussionmentioning
confidence: 99%
“…The American College of Sports Medicine recommends at least 200 minutes per week of moderate‐intensity exercise (~1200 MET‐minutes/week, comparable to our DE group and significantly more than our LI group) to prevent weight regain . Physical activity level protects against development of NAFLD independent of insulin resistance and visceral adiposity, underscoring the importance of continued regular exercise to prevent accumulation of hepatic fat. Successful weight‐loss interventions in NAFLD studies involved individual counselling, goal setting and assessment every 3‐12 months, and staff contacts up to 20 times annually…”
Section: Discussionmentioning
confidence: 68%
“…40 The American College of Sports Medicine recommends at least 200 minutes per week of moderate-intensity exercise (~1200 MET-minutes/week, comparable to our DE group and significantly more than our LI group) to prevent weight regain. 18 Physical activity level protects against development of NAFLD independent of insulin resistance and visceral adiposity, 41 were found to be more responsive biomarkers compared to histology 42 and cCK-18 changes have been correlated with histological progression. 25 MRI elastography has been validated as a non-invasive measure of fibrosis 20 .…”
Section: Assessment For Eligibilitymentioning
confidence: 99%
“…129 A recent prospective cohort study from our group demonstrated a lower risk of incident NAFLD in 4 years of follow-up based on physical activity level at baseline. 130 Furthermore, sustained or increased physical activity had a preventive effect on incident NAFLD, independent of visceral adiposity and insulin resistance. 130 In summary, increased physical activity is an important component of lifestyle modification in patients with NAFLD and comorbid extrahepatic manifestations, irrespective of visceral obesity or insulin resistance.…”
Section: Physical Activitymentioning
confidence: 97%